2018
DOI: 10.25100/cm.v49i4.3515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high-grade perineal tear during labor in Mexican adolescents

Abstract: Introduction: There is a high rate of deliveries in adolescents in Mexico. This age group is vulnerable to obstetric complications, including lacerations of the anal sphincter.Objective: To determine the prevalence of third and fourth degree perineal tears in adolescents during childbirth, and to evaluate risk factors in comparison with deliveries with lacerations of adult women.Methods: All obstetric care episodes were reviewed from a public tertiary hospital data in Monterrey, Mexico in 2014. Age, primiparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Adolescents accounted for 60 cases (33.5%), for a prevalence of 2.5% of tears in this age group, higher than the prevalence of adult women (1.8%). 19 The results of our study indicate that the most common indication for caesarean section in adolescent mothers was fetal asphyxia (28.0%).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Adolescents accounted for 60 cases (33.5%), for a prevalence of 2.5% of tears in this age group, higher than the prevalence of adult women (1.8%). 19 The results of our study indicate that the most common indication for caesarean section in adolescent mothers was fetal asphyxia (28.0%).…”
Section: Discussionmentioning
confidence: 62%
“…There was a downward trend of pregnancies in the study groups. Complications related to pregnancy and childbirth are the main cause of death of[15][16][17][18][19]…”
mentioning
confidence: 99%
“…The search scheme is shown in Figure 1. As for the year of publication, 2 were published in 2014, 3,4 7 in 2015, [5][6][7][8][9][10][11] 6 in 2016, [12][13][14][15][16][17] 8 in 2017, [18][19][20][21][22][23][24][25] 5 in 2018, [26][27][28][29][30] 17) and 1 that did not specify the method of data collection. 14 The studies had age groups for adolescents and for the control group variables.…”
Section: Resultsmentioning
confidence: 99%
“…Although over the past years the mean age of Romanian women at the birth of the first child has been constantly increasing, 11.2% of first-born babies in 2019 belonged to mothers of 10 to 19 years of age [ 6 , 7 ]. Teenage mothers represent a vulnerable group for the development of high-grade perineal tears during spontaneous vaginal birth [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified primiparity, fetal weight higher than 4000 g, operative delivery, the prolonged second stage of labor, and shoulder dystocia as the most often cited risk factors for severe lacerations [ 14 ]. Specifically, in the adolescent population, risk factors for perineal tears of primiparity, fetal position, gestational diabetes, and duration of the second stage of labor have already been documented [ 8 ]. The long-term complications associate medico-legal repercussions and increased health care costs, especially since studies on young women with pelvic floor symptoms proved that they may be at risk for increased severity of these conditions later in life [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%